Flat midsubstance of the anterior cruciate ligament with tibial "C"-shaped insertion site - Siebold, Rainer; Schuhmacher, Peter; Fernandez, Francis; Smigielski, Robert; Fink, Christian; Brehmer, Axel; Kirsch, Joachim (Knee Surgery Sports Traumatology Arthroscopy, 2015)
This anatomical cadaver study was performed to investigate the flat appearance of the midsubstance shape of the anterior cruciate ligament (ACL) and its tibial "C"-shaped insertion site.The ACL midsubstance and the tibial ACL insertion were dissected in 20 cadaveric knees (n = 6 fresh frozen and n = 14 paraffined). Magnifying spectacles were used for all dissections. Morphometric measurements were performed using callipers and on digital photographs.In all specimens, the midsubstance of the ACL was flat with a mean width of 9.9 mm, thickness of 3.9 mm and cross-sectional area of 38.7 mm(2). The "direct" "C"-shaped tibial insertion runs from along the medial tibial spine to the anterior aspect of the lateral meniscus. The mean width (length) of the "C" was 12.6 mm, its thickness 3.3 mm and area 31.4 mm(2). The centre of the "C" was the bony insertion of the anterior root of the lateral meniscus overlayed by fat and crossed by the ACL. No posterolateral (PL) inserting ACL fibres were found. Together with the larger "indirect" part (area 79.6 mm(2)), the "direct" one formed a "duck-foot"-shaped footprint.The tibial ACL midsubstance and tibial "C"-shaped insertion are flat and are resembling a "ribbon". The centre of the "C" is the bony insertion of the anterior root of the lateral meniscus. There are no central or PL inserting ACL fibres. Anatomical ACL reconstruction may therefore require a flat graft and a "C"-shaped tibial footprint reconstruction with an anteromedial bone tunnel for single bundle and an additional posteromedial bone tunnel for double bundle.
EVALuna2:4153